Problems Synthesis representation through Activity Inquiry-Link Maps for Analyzing the Thermodynamics Conceptual Change - Anis Fahrurotul Futihat (Pascasarjana Universitas Negeri Malang (UM), 2014)
Representasi Synthesis Problems melalui Aktivitas Inquiry-Link Maps untuk Menganalisis Perubahan Konseptual TermodinamikaAbstract: The objective of this study is to analyze students’s conceptual change after learning activity by inquiry-link maps model. Conceptual change is measured by analyzing both link maps and synthesis problems-representation created by students. The study used embedded research design while conducted on the class consisting of 25 students. After intervention, we obtained that: (1) there is a change in students conceptual, (2) link maps created by students is more structured, (3) synthesis problems-representation is better. Key Words: synthesis problems-representation, activity, inquiry-link maps, thermodynamics concep-tual changesAbstrak: Telah dilakukan penelitian analisis perubahan konseptual yang dibentuk siswa setelah dilaksanakan pembelajaran model inquiry-link maps. Perubahan konseptual diukur melalui analisis terhadap link maps dan representasi synthesis problems yang dibuat siswa. Penelitian ini menggunakan metode embedded research design dan dilakukan pada satu kelas yang terdiri dari 25 siswa. Setelah intervensi diperoleh hasil: (1) terdapat perubahan konseptual pada siswa, (2) link maps menjadi lebih terstruktur, (3) representasi synthesis problems menjadi lebih baik. Kata kunci: representasi synthesis problems, aktivitas, inquiry-link maps, perubahan konseptual termodinamika